A STUDY ON FORCED DEGRADATION AND VALIDATION OF STABILITY INDICATING RP-HPLC METHOD FOR DETERMINATION OF BENZALKONIUM CHLORIDE IN AZELASTINE HYDROCHORIDE PHARMACEUTICAL OPHTHALMIC FORMULATION - Gupta, Pratik Kumar; Chaturvedi, Vibha (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Objective: This study was designed to conduct forced degradation and validation studies for determination the benzalkonium chloride (BKC) as major homologues form in azelastine hydrochloride pharmaceutical ophthalmic formulation by a novel stability indicating reverse phase high-performance liquid chromatographic method (RP-HPLC). Methods: Forced degradation study and validation were carried out with a analytical approach of reverse phase chromatographic analysis with C18, cosmosil (250mm x 4.6mm i.d. x 5μm) column using mobile phase consisting acetonitrile – buffer of pH 5.0 with 5N NaOH (45:55 %v/v) at a flow rate of 1.5 ml per minute. Column temperature was maintained at 25°C and detection wavelength was 210nm.By using these chromatographic conditions of method, two major homologues of benzalkonium chloride were separated without any interference of drug components and exciepients. Results: Forced degradation studies were carried out as per ICH guidelines and established a stability indicating property of a method .The method was found linear in concentration range 40μg/ml to 60μg/ml (50μg/ml±20%), correlation coefficient was found 0.999. The recovery was found to be 99.2%, 100.7% and 101.4% at ±30% of target concentration. The %RSD for method precision and intermediate precision were found 0.28% and 0.30 % respectively. The method was found specific, selective, precise, accurate, linear, robust and stability indicating for quantification benzalkonium chloride in azelastine pharmaceutical ophthalmic formulation. Conclusion: The method has been found successful for determination of BKC pharmaceutical formulation and validated for all the parameters of validation and found within the acceptance criteria as per ICH guideline Q2R1.